The Fight against Organised Crime in Serbia and International Police Cooperation - Zoran, Đurđević; Nenad, Radović; Željko , Nikač (Magyar Rendészet, 2025)
This report outlines the legislative framework and institutional mechanisms in the fight against organised crime, as well as international police cooperation between the Republic of Serbia and its foreign partners. The legislative framework includes key international and national sources, particularly the Palermo Convention against Organized Crime, the Law on the Organisation and Competencies of State Bodies in the Fight against Organised Crime, Terrorism and Corruption, the Criminal Procedure Code, the Criminal Code and the Law on Confiscation of Property Acquired through Crime, among others. Institutional mechanisms crucial for combatting organised crime encompass various forms of police and intelligence operations alongside various authorities, organisations and agencies. In the final section, the report offers several proposals for enhancing the legislative framework and the operational practices of police and law enforcement agencies. Given Serbia’s application for EU membership, the importance of aligning national laws with EU regulations in the fight against organised crime and other serious criminal activities is particularly emphasised.